Treatment modality of impacted central incisor associated with dentigerous cyst and compound odontome - Pandey, Bashu Raj; Subedi, Sushil; Shrestha, Bijayata; Chaulagain, Rajib (Journal of Chitwan Medical College, 2018)
Impacted tooth is frequently encountered in dental practice. But the impacted tooth associated with supernumerary tooth and dentigerous cyst in anterior region is very rare case. The present case reports the successful management of impacted right central incisor with multiple odontome and dentigerous cyst by surgical intervention and orthodontic extrusion. Close eruption technique was applied after enucleation of cyst and extraction of odontome. Thirty grams traction force was applied after bonding in the labial surface of impacted tooth. Subsequently fixed orthodontic technique was applied to get impacted central incisor into occlusion.